Herbarium survey of African Corchorus L. species - Edmonds, J.M. (1990)
A general survey of Corchorus L. species was commissioned by the International Jute Organization (IJO) to provide the necessary background data on which future germplasm-collecting expeditions could be based. The survey was required to identify those wild species of potential use in the future genetic improvement of jute, in addition to identifying the countries and locations where collecting expeditions would be most profitable.